Early Modern Litterae Indipetae for the East Indies - Frei, Elisa (Brill, 2023)
During the early modern period, thousands of Jesuits across Europe wrote individual applications for appointments in the "Indies" directly to the superior general of the Society of Jesus in Rome. Known today as litterae indipetae (from Indias petere, that is, applying for the missions in the Eastern and Western territories), these letters encompassed the most personal desires, hopes, and dreams of young Jesuits who sought to become missionaries. This book is the first English monograph on litterae indipetae and studies their style and structure, the background of their authors and the reasons behind their choices, as well as the network surrounding this practice (natural and spiritual families, procurators, confrères). Its purpose is also to capture the experiences of these individuals since lost to history by studying thousands of indipetae, in this case written mainly by Italian Jesuits at the turn of the eighteenth century. It focuses especially on the petitions aimed at East Asia, and offers in-depth analysis of cases of Jesuits whose missionary zeal for China and Japan was fulfilled-or not.